Technologies of Modern Reindeer - Vladislava Vladimirova (Norsk Antropologisk Tidsskrift)
Abstract This article explores how reindeer science in Circumpolar Russia is a field of constitutions of indigenous people and animal subjectivities. It is based on empirical research of selective breeding of the Evenki breed of reindeer in the specialised Soviet literature and in the Reindeer Herding Enterprise in the village of Surinda, Evenki Municipality. Reindeer herding has historically played a significant role for the majority indigenous Evenki people. Neat classification of reindeer into distinctive breeds was completed in Soviet time, when “proper” selective breeding technologies were established. This article looks into some of the basic assumptions about animals, humans, and society that such breed classification and selection methods reveal. I analyse the role of scientific knowledge in the Soviet era to better understand why selective reindeer breeding appears more attractive to state authorities than to support indigenous reindeer husbandry, which has been experiencing a serious crisis since the early 1990s. I explain the local politics of reindeer herding and agricultural science through the contextualisation of the field case within Soviet and contemporary Russian Arctic and indigenous governance, trying to contribute to the broader issue of post-Soviet perceptions of animal husbandry, selective breeding and reindeer.